Impact of Organizational Citizenship Behavior on Talent Management with Mediating Role of Organizational Commitment: Evidence From Pakistani Universities - Neelam Akbar; Ammara Murtaza; Muhammad Anees Ul Husnain Shah; Jawad Karamat; Shabana Akbar; Nazim Ali (Kurdish Studies, 2024)
This research examines the relationship between Organizational Citizenship Behavior (OCB) and Talent Management (TM) with Organizational Commitment (OC) as the mediator in faculty members of Pakistan’s universities. A quantitative research was used in this study and data was collected through structured questionnaires from 527 faculty members. The results of descriptive statistics as well as correlation and regression analysis showed that there is a positive correlation between OCB, OC and TM. Consequently, it is ascertained that engaging faculty members in OCB will increase the level of commitment towards one Institution and increase the TM practice. It has been found that there is a strong positive relationship between OCB and TM and it has been measured to be equal to 0.503. Indicating that the faculty members in these universities under study are committed to assist with talent development and management. The paper thus emphasizes the need to promote a work culture of teamwork, and commitment and incorporate OCB into TM to increase organizational performance. These results offer practical implications for universities’ TM practices to promote voluntary behaviors and reinforce OC.